The legal relevance of man-made constructions in maritime zones - Trappler, Gary (Institute of Marine and Environmental Law, 2023)
Maritime zones simply, are imaginary lines in the ocean which serve to divide one area of the sea from another, with each area conferring differing rights and obligations on those persons or states utilising such area. The lines of demarcation are imaginary in the sense that they cannot be observed (as opposed to natural dividing lines on land such as rivers, mountains or even fences) but they are real in the sense that they exist, and recognition of their existence is vital for all coastal states and sea faring nations.